Comparative analysis of certification requirements for land managers and geodesists in Ukraine and Poland - Kharytonenko, R.; Vysidalko, A.; Trokhymchuk, A. (Land Management, Cadastre and Land Monitoring, 2021)
The analysis of scientific researches concerning professional training and qualification certification of engineers-land surveyors in Ukraine and abroad is carried out. The need to study, borrow the experience of one of the countries of the European Union and further adapt this certification in Ukraine is substantiated.Qualification requirements for certification of land surveying engineers in Ukraine and Poland are considered. A comparison of the qualification exam for a certified land surveyor is given. An analysis of the comparison of similar and different indicators for obtaining a certificate of land surveying engineer in Ukraine and Poland. Emphasis is placed on the quality of qualification selection of certified land surveyors.The proposals in the revision of the requirements for obtaining a qualification certificate of a land surveyor in Ukraine are given. In the future, the revision of the qualification certification requirements will help create objective equal opportunities for land relations specialists, improve the quality of land management documentation, as well as facilitate the adaptation of certification with our western neighbors - the European Union.Key words: certificate of land surveyor, certification, land management, surveying engineers, foreign experience, professional practice.